Faktor-Faktor Yang Mempengaruhi Audit Delay Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014 - Nurma Gupita Putri, Dinar (2016)
ABSTRACT Audit delay or audit report lag is what can affect the accuracy of the information published , which will affect the level of uncertainty a decision based on published information. Timeliness of financial statements audit is very important , especially for public companies that use capital markets as a source of funding . The purpose of this research is to analyze and examine the factors that affect the size of the company , profit / loss of operation , solvency , profitability , the auditor's opinion , the reputation of the auditor to audit delay on manufacturing companies listed in Indonesia Stock Exchange . Samples were 111 companies listed on the Indonesian Stock Exchange from the year 2012-2014 with a sample method in use is purposive sampling .This method of data analysis is descriptive analysis test analysis assumption and multiple regression analysis to test the hypothesis. Results of this research is the effect on the solvency of the audit delay . While the size of the company , the profit / loss of operations, profitability , the auditor's opinion , the auditor 's reputation has no effect on audit delay . Keywords : Audit Delay , Company Size , Profit / Loss of operations, Solvency.